2012
DOI: 10.1016/j.cell.2011.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Promoter-Centered Chromatin Interactions Provide a Topological Basis for Transcription Regulation

Abstract: Summary Higher-order chromosomal organization for transcription regulation is poorly understood in eukaryotes. Using genome-wide Chromatin Interaction Analysis with Paired-End-Tag sequencing (ChIA-PET), we mapped long-range chromatin interactions associated with RNA polymerase II in human cells and uncovered widespread promoter-centered intra-genic, extra-genic and inter-genic interactions. These interactions further aggregated into higher-order clusters, wherein proximal and distal genes were engaged through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

90
1,287
4
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,132 publications
(1,416 citation statements)
references
References 46 publications
90
1,287
4
9
Order By: Relevance
“…Of these interactions, 2 373 involved enhancer-promoter interactions. Interestingly, a substantial number of the detected interactions, 3 669, were distal promoter-promoter interactions, a finding consistent with results using RNA Polymerase II to detect interactions [11]. The remaining 478 interactions were reported to be enhancer-enhancer interactions.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Of these interactions, 2 373 involved enhancer-promoter interactions. Interestingly, a substantial number of the detected interactions, 3 669, were distal promoter-promoter interactions, a finding consistent with results using RNA Polymerase II to detect interactions [11]. The remaining 478 interactions were reported to be enhancer-enhancer interactions.…”
supporting
confidence: 71%
“…As enhancers can be highly cell type specific [2,3], having interaction maps in additional cell types and conditions will be a valuable resource. Such interaction maps would likely yield insights into the dynamics of gene regulation and into the mechanisms by which individual distal regulatory variants act to confer disease risk [11]. Genomics has been largely centered on a one-dimensional representation of the genome, but this work by Chepelev et al [12] and recent work by others represent important steps towards mapping and understanding the higher dimensional nature of the genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the ratio between H3K4me3 and H3K4me1 indicates the tendency of the region to act as either a promoter or an enhancer (74). To classify the differential regions as enhancers or promoters, we used a published dataset, which includes both H3K4me3 and H3K4me1 ChIP-seq data of mouse embryonic stem cells (75).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, DNA looping facilitates gene network formation as a single enhancer may interact with more than one promoter, and a single promoter may be contacted by more than one enhancer. Many of these interactions occur in a tissue‐specific manner and appear to be the major determinants of cell type‐specific responses 111, 113, 114, 115. Critically, many enhancers do not interact with the nearest active gene but contact gene promoters many hundreds to thousands of kilobases away through long‐range DNA looping (modelled for T cells in Figure 8).…”
Section: Enhancer–promoter Interactions Shape the Function Of Tregmentioning
confidence: 99%